Lime and manure amendment improve soil fertility, productivity and nutrient uptake of rice-mustard cropping pattern in an acidic terrace soil - Islam, Mohammad Rafiqul; Hasan Talukder, Mohammad Moyeed; Hoque, Mohammad Anamul; Uddin, Shihab; Hoque, Tahsina Sharmin; Rea, Rafea Sultana; Alorabi, Mohammed; Gaber, Ahmed; Kasim, Susilawati (MDPI AG, 2021)
Acid soil is an obstacle to agricultural development and a concern regarding food and environmental security. Therefore, a study was carried out for two consecutive years to see how lime and organic manure (OM) amendments affect yield and nutrient absorption in the Transplanted (T.) Aman–Mustard–Boro cropping pattern in an acidic terrace soil. With nine treatments and three replications, the experiment was set in a randomized complete block design. The treatments were applied to the first crop, T. Aman, with different dosages of lime (dololime at the rate of 1 and 2 t ha−1), OM (cow dung at 5 t ha−1, poultry manure at 3 t ha−1) and lime–OM combination, and their residual effects were studied in the following mustard and boro rice crops. Results demonstrate that the effect of lime and manure was more pronounced in the case of the second and third crops in the first year and of all crops in the pattern in the second year. In the first year, grain and straw yield of T. Aman as well as the overall system productivity were not influenced significantly by the application of lime and manure, but significant increases were obtained in the second year. As an average of both years, the highest grain yield of 5.2 t ha−1 (12% over control) was recorded for T. Aman, 1.7 t ha−1 (41% over control) for mustard and 5.9 t ha−1 (47% over control, 3.9 t ha−1) for boro rice when dololime was applied in combination with poultry manure. In both years, N, P, K and S uptake were significantly increased compared to the control in all the crops due to the combined application of lime and cow dung or poultry manure. Combined application of lime and manure amendment significantly improved nutrient availability and soil quality. Therefore, applying lime in combination with manure can be practiced to uplift crop productivity in acidic terrace soils.